Clinical trial to develop Ayurved protocol in Snayugata Aaghataja Shotha with special reference to ankle sprain (AYUSHDHARA, 2024)
Acute sprains from sports injuries frequently occur in the ankle joint. Acute ankle sprain is responsible for 10-30% of sports related injuries in young athletes. Ankle sprain symptoms include pain and swelling, either with or without deformity. Modern science developed treatment modalities for the ankle sprain are below knee cast, ankle brace and ankle strap. When an ankle sprain is not treated properly, it can lead to chronic problems like pain, instability in the joint and limited range of motion.Acharya Sushruta suggests Alepa with Sandhaniya Dravyas for the management of Snayugata Shotha. When employed as a Lepa, these Dravyas possess the qualities of Sandhaniya, Shodhahara, and Vedanashaman action.It is need of today era to develop Ayurvedic protocol for ankle sprain. Hence, this study is taken up to develop protocol according to Ayurved. Phase wise distribution of Lepa, Patta Bhandhan mentioned in this article.